In vitro histomechanical effects of enzymatic degradation in carotid arteries during inflation tests with pulsatile loading. (March 2020) - Trabelsi, Olfa; Dumas, Virginie; Breysse, Edouard; Laroche, Norbert; Avril, Stephane
Abstract : In this paper, the objective is to assess the histomechanical effects of collagen proteolysis in arteries under loading conditions reproducing in vivo environment. Thirteen segments of common porcine carotid arteries (8 proximal and 5 distal) were immersed in a bath of bacterial collagenase and tested with a pulsatile tension/inflation machine. Diameter, pressure and axial load were monitored throughout the tests and used to derive the stress-stretch curves and to determine the secant circumferential stiffness. Results were analysed separately for proximal and distal segments, before and after 1, 2 and 3 h of enzymatic degradation. A histological analysis was performed to relate the arterial microstructure to its mechanical behavior under collagen proteolysis. Control (before enzymatic degradation) and treated populations (after 1, 2 or 3 h of enzymatic degradation) were found statistically incomparable, and histology confirmed the alteration of the fibrous structure of collagen bundles induced by the collagenase treatment. A decrease of the secant circumferential stiffness of the arterial wall was noticed mostly at the beginning of the treatment, and was less pronounced after 1 h. These results constitute an important set of enzymatically damaged arteries that can be used to validate biomechanical computational models correlating structure and properties of blood vessels.